2013
DOI: 10.1039/c3cc44256j
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid-functionalized fluorescent gold nanoclusters with polymers as linkers for cancer cell imaging

Abstract: A novel nano-conjugate containing ultrasmall water-soluble AuNCs protected by ovalbumin as the fluorescent part, folic acid as the targeting ligand and a homopolymer N-acryloxysuccinimide as the linker has been investigated. Moreover, specific staining of HeLa cells by the nano-conjugate has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 14 publications
(12 reference statements)
1
84
0
Order By: Relevance
“…1,3 Due to their ultra small size, excellent luminescence properties, and stable structures, Au NCs have attracted significant attention in the past decade. [2][3][4][5] Chen et al 6 determined the enzyme activity by assessing the change in emission intensity of fluorescent Au NCs, Qiao et al 7 reported that ovalbumin-protected Au NCs with folic acid can be used for HeLa cells imaging, and Yue et al 8 synthesized bovine serum albumin-capped Au NCs as a fluorescence probe to determine nitrite (NO 2 -) sensitively and selectively. Inorganic nanoparticles are difficult to biodegrade and induce long-term toxicity, which hinders their application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Due to their ultra small size, excellent luminescence properties, and stable structures, Au NCs have attracted significant attention in the past decade. [2][3][4][5] Chen et al 6 determined the enzyme activity by assessing the change in emission intensity of fluorescent Au NCs, Qiao et al 7 reported that ovalbumin-protected Au NCs with folic acid can be used for HeLa cells imaging, and Yue et al 8 synthesized bovine serum albumin-capped Au NCs as a fluorescence probe to determine nitrite (NO 2 -) sensitively and selectively. Inorganic nanoparticles are difficult to biodegrade and induce long-term toxicity, which hinders their application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Labeling of biomolecules is the key basis of AuNCs for their further biomedical applications [65,66]. Such bioconjugations commonly depend on adsorption, chelation, and covalent interaction.…”
Section: Functionalization Of Auncsmentioning
confidence: 99%
“…In addition, a competition experiment was carried out by adding a certain amount of free FA before FA-TiO 2 and TiO 2 treatment [25].…”
Section: Targeting Ability Of Fa-tiomentioning
confidence: 99%